Comprehension and Use of English Article by Urdu L1 Speakers in Pakistan - Yasmeen, Iqra; Nazeer, Musarat; Pervaiz, Azhar (JELLL, 2024)
The focus of this study is to find out the production and comprehension of definite and indefinite articles for the given and the new referents. The study involves 52 graduates and post-graduates aged eighteen to twenty-five years with normal language skills from the University of Sargodha (UOS). There are two parts of the study done in this paper, one is the production task which is based on a picture story (Schroder, Gemballa, Ruppin & Wartenburger, 2012), and the other task is the comprehension task which follows van Hout et al (2010) through the truth-value judgment task. The instrument of the study i.e. the questionnaire is divided into three parts. The third part of the questionnaire consists of the truth value judgment task, in which participants choose the right option by looking at the picture. Production and comprehension of the definite and indefinite articles as a mark of givenness show that participants have a better understanding of given referents as compared to the new referents. The results show that most of the participants responded with the right option for the given referents.